Strategic management accounting as an information platform for measuring innovation of the enterprise - Bondar, Mykola; Iershova, Natalia; Chaika, Tetiana (SHS Web of Conferences, 2019)
The study provides an integrated analysis system of the innovative activity of the enterprise, generalized mechanism of information processing in the accounting and analytical system of the enterprise. The role of information of strategic management accounting and analysis in the accounting and analytical system of the enterprise is substantiated. The bimodal methodological approach to measuring innovation of the enterprise on the basis of an integral performance exposure, calculated on a set of partial indicators, using additive method was introduced.

В даному дослідженні представлена комплексна система аналізу інноваційної активності підприємства, узагальнено механізм обробки інформації в обліково-аналітичній системі підприємства. Обґрунтовано роль інформації стратегічного управлінського обліку та аналізу в обліково-аналітичній системі підприємства. Запроваджено бімодальний методологічний підхід до вимірювання інновацій підприємства на основі інтегральної оцінки ефективності, розрахованої за сукупністю часткових показників з використанням адитивної методу.
Стратегічний управлінський облік як інформаційна платформа для оцінки інноваційної активності підприємства
Keywords: strategic management accounting; innovative activity; accounting and analytical system; sustainable development strategy; effectiveness of management decisions; accounting information; стратегічний управлінський облік; інноваційна активність; обліково-аналітична система; стратегія сталого розвитку; ефективність управлінських рішень; облікова інформація